Highly Stable Lithium Metal Batteries Enabled by Regulating the Solvation of Lithium Ions in Nonaqueous Electrolytes - Zhang, Xue‐Qiang; Chen, Xiang; Cheng, Xin‐Bing; Li, Bo‐Quan; Shen, Xin; Yan, Chong; Huang, Jia‐Qi; Zhang, Qiang (Angewandte Chemie International Edition, 2018)
Safe and rechargeable lithium metal batteries have been difficult to achieve because of the formation of lithium dendrites. Herein an emerging electrolyte based on a simple solvation strategy is proposed for highly stable lithium metal anodes in both coin and pouch cells. Fluoroethylene carbonate (FEC) and lithium nitrate (LiNO3) were concurrently introduced into an electrolyte, thus altering the solvation sheath of lithium ions, and forming a uniform solid electrolyte interphase (SEI), with an abundance of LiF and LiNxOy on a working lithium metal anode with dendrite‐free lithium deposition. Ultrahigh Coulombic efficiency (99.96 %) and long lifespans (1000 cycles) were achieved when the FEC/LiNO3 electrolyte was applied in working batteries. The solvation chemistry of electrolyte was further explored by molecular dynamics simulations and first‐principles calculations. This work provides insight into understanding the critical role of the solvation of lithium ions in forming the SEI and delivering an effective route to optimize electrolytes for safe lithium metal batteries. Not dead ′Li′: Fluoroethylene carbonate (FEC) and lithium nitrate (LiNO3) were concurrently introduced into an electrolyte, thus altering the solvation sheath of lithium ions and forming a uniform solid electrolyte interphase (SEI). An abundance of LiF and LiNxOy is formed on the working lithium metal anode and contributes to dendrite‐free lithium deposition.